A highly sensitive ECL platform based on GOD and NiO nanoparticle decorated nickel foam for determination of glucose in serum samples. Issue 12 (13th March 2020) - Kamyabi, Mohammad Ali; Moharramnezhad, Mohsen
Abstract : The mechanism of ECL glucose biosensor based on GOx/NiONPs/Ni-foam. Abstract : In this work, a new ECL glucose biosensor was fabricated based on immobilized glucose oxidase into the cavity of the nickel foam modified with nickel oxide nanoparticles. The nickel oxide nanoparticles were deposited on the surface of 3-D Ni-foam by a simple electrochemical method. On the other hand, due to the porous structure of the nickel foam, the enzyme was well inserted into the cavities of the Ni-foam. Hydrogen peroxide intensified the optical signal of luminol, which is produced during the reaction of glucose oxidase and glucose in the presence of oxygen. Also, the nickel oxide nanoparticles exhibited superior electrocatalytic properties in the oxidation of the luminol. The nickel oxide nanoparticle modified Ni-foam electrode was characterized using electrochemical impedance spectroscopy, field emission scanning electron microscopy, energy-dispersive X-ray spectroscopy, X-ray photoelectron spectroscopy, and X-ray diffraction. The modified electrode was successfully used for the quantification of glucose by an electrochemiluminescence method. The proposed ECL biosensor showed superior performance toward glucose in 0.1 M phosphate buffer solution pH 7.4 with a wide linear range (2.7 × 10 −9 to 4.5 × 10 −3 M) and a low detection limit (5.0 × 10 −10 M). Due to the good immobilization of the enzyme, the presented biocomposite exhibited remarkable performance for sensitive detection of glucose with high selectivity and good reproducibility. Thus, it has been utilized for glucose analysis in human serum samples with acceptable outcomes.